The Incidence, Risk Factors and Diagnosis of Ventilator Associated Penumonia. - Karim, Amer S.; Sultan, Kassim M.; Al- Obaidy, Muhammed W. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: The critically ill patient is at risk of developing intensive care acquired infection, with the lungs being especially vulnerable. Ventilator associated pneumonia (VAP) occurring after two days of mechanical ventilation and it is the most nosocomial infection seen in the intensive care unit .The establishment of an accurate diagnosis of ventilator associated pneumonia remains problematic and yet there is still no accepted "gold standard" for the diagnosis.Patients& Methods: This is a cross section study for 328 patients admitted to intensive care unit at medical city teaching hospital. Full history, physical examination and investigation were done after 48 hours of admission according to clinical pulmonary infection score using clinical criteria (body temperature, WBC count, oxygenation, chest radiography and tracheal aspiration).Arterial blood gases were taken for all patients.Results: 40 patients developed ventilation associated pneumonia out of 328 patients (12.19%) treated intensive care unit. Most patients who developed pneumonia were at extreme of age and there was no association between the disease and gender. The presence of risk factors like invasive mechanical ventilation (97.5%) nasogastric intubation (90%), tracheostomy (75%), post-operative (30%),insertion of urinary catheter (75%) unconscious patients (57.5%) and vomiting (27.5%) were found as an important risk factors .Gram negative bacteria was the most frequently observed especially pseudomonas aeruginosa (40%) klebsiella (15%)..Conclusion: ventilator associated pneumonia is an important cause of mortality. The clinical pulmonary infection score was found to be the reliable method for diagnosis of ventilator associated pneumonia. There is general agreement that rapid initiation of appropriate antimicrobial therapy will improve the outcome.